(untitled) (Marketing Journal, 2026)
This comprehensive study examines the critical role of strategic management in enhancing tourism destination competitiveness within the contemporary global tourism landscape. As international tourism continues to evolve amid increasing competition, technol ogical disruption, and changing consumer preferences, destinations must adopt sophisticated strategic approaches to maintain and improve their competitive positions. This research employs a mixed -methods approach, combining quantitative analysis of destina tion competitiveness indicators with qualitative case study examination of successful strategic interventions. The study analyzes data from 45 tourism destinations across different development stages, examining the relationship between strategic management practices and competitive performance outcomes. Findings reveal that destinations implementing comprehensive strategic management frameworks demonstrate significantly higher competitiveness scores across multiple dimensions including infrastructure develo pment, marketing effectiveness, sustainability practices, and stakeholder coordination. The research identifies five critical success factors for strategic destination management: integrated planning systems, dynamic capability development, stakeholder eng agement mechanisms, innovation orientation, and adaptive governance structures. Results indicate that strategic management implementation can improve destination competitiveness indices by 23 -47% over five -year periods when properly executed. The study contributes to theoretical understanding of destination competitiveness determinants while providing practical frameworks for destination management organizations seeking to enhance their competitive positions in increasingly challenging market environments.